La Sodeci, Un Outil Strategique Dans La Distribution D’eau Potable En Cote d’Ivoire - Koffi, Atta; Abou, Diabagate; Ghislaine, Konan Honorée (European Scientific Journal, ESJ, 2016)
This study aims to make SODECI (water distribution) better known by the Ivorian populations. Indeed, very few studies have been made on it to make it known. Therefore, this study raises the problem of ignorance of this strategic tool in the supply of drinking water in Côte d’Ivoire. To solve this problem, a methodology based on documentary research and interview has allowed to track its development route. Thus, from its creation, it will undergo a remarkable development but it will later face crises that will affect it without undermining its fundamentals. Until late 2015, it served 964 villages and 13,745,067 inhabitants that is a national coverage of 68%. The fruit of his prowess is put to the credit of an exceptional managerial policy and a civic attitude during the Ivorian crisis that rocked and split the country in 2002.